2008
DOI: 10.1038/sj.bjc.6604667
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the systemic inflammatory response, tumour proliferative activity, T-lymphocytic and macrophage infiltration, microvessel density and survival in patients with primary operable breast cancer

Abstract: The significance of the inter-relationship between tumour and host local/systemic inflammatory responses in primary operable invasive breast cancer is limited. The inter-relationship between the systemic inflammatory response (pre-operative white cell count, C-reactive protein and albumin concentrations), standard clinicopathological factors, tumour T-lymphocytic (CD4 þ and CD8 þ ) and macrophage (CD68 þ ) infiltration, proliferative (Ki-67) index and microvessel density (CD34 þ ) was examined using immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 41 publications
4
58
0
1
Order By: Relevance
“…The data suggest that macrophages predominate in inflammatory infiltrates, with significant implications for angiogenesis in breast cancer, which has been attributed, in part, to the secretion of proangiogenic factors by macrophages. 56 Consistent with previously published observations, expression of the myeloid cell marker CD68 57 was a weak adverse prognostic factor in univariate analyses of overall survival, but not relapsefree survival. Expression of DC-SIGN, an immature myeloid dendritic cell marker, was also a significant prognostic factor in univariate analyses of overall survival, but not relapse-free survival.…”
Section: Discussionsupporting
confidence: 89%
“…The data suggest that macrophages predominate in inflammatory infiltrates, with significant implications for angiogenesis in breast cancer, which has been attributed, in part, to the secretion of proangiogenic factors by macrophages. 56 Consistent with previously published observations, expression of the myeloid cell marker CD68 57 was a weak adverse prognostic factor in univariate analyses of overall survival, but not relapsefree survival. Expression of DC-SIGN, an immature myeloid dendritic cell marker, was also a significant prognostic factor in univariate analyses of overall survival, but not relapse-free survival.…”
Section: Discussionsupporting
confidence: 89%
“…In line with this, we found that loss of p120 results in the development of stromal dense and macrophage-rich mammary tumors. Furthermore, we show that loss of p120 leads to secretion of several cytokines, which may control the recruitment of inflammatory cells (e.g., macrophages) that have been implicated in inflammation-associated cancer initiation and promotion (48) and are correlated with poor prognosis in breast cancer (49,50). Moreover, it has been well established that mammary tumor cells may instigate a paracrine loop that involves the production of chemoattractants and subsequent recruitment of EGF-producing macrophages, resulting in activation of prometastatic pathways in tumor cells (51,52).…”
Section: Loss Of P120 Results In a Prometastatic Microenvironmentmentioning
confidence: 90%
“…In addition, the clinical stage of breast cancer was determined to be a major contributor to a poor prognosis. Similarly, Murri et al (15) reported the expression of CD34 in 168 patients with early invasive breast cancer. This study identified that an increased tumor MVD was correlated with the OS of the patients (P<0.05), and multivariate analysis identified albumin concentration, topical therapy, systemic therapy and tumor MVD as independent factors for predicting a poor prognosis (P<0.05).…”
Section: Discussionmentioning
confidence: 87%